ORGANIZATIONAL, LEGAL AND METHODOLOGICAL ASPECTS OF DETERMINING THE NUMBER OF PERSONNEL UNITS IN THE NATIONAL GUARD OF UKRAINE - Kaidalov, Ruslan; Morkvin, Dmytro; Batsamut, Volodymyr (Honor and Law, 2023)
The study examines the organizational and legal aspects of the activities of personnel units in the National Guard of Ukraine. The main directions of personnel support of National Guard of Ukraine have been determined. The rules for calculating the strength of personnel units at the Regional Command, brigade, battalion level are defined. It was emphasized that the legal support for the activities of personnel units of National Guard of Ukraine needs significant improvement within the framework of Ukraine’s movement towards joining NATO and ensuring the J-1 standard. The legal acts regulating the accounting of personnel at National Guard of Ukraine were considered and the corresponding changes to them were proposed. It is determined that human resources units and personnel accounting units perform related and interrelated functions and must be under a single command within a department, section, service, etc. An example of determining the sufficient number of personnel of the personnel work unit is given on the example of the simulated operational assignment brigade of National Guard of Ukraine.